The Role of Neologisms in Mass Media and Social Networks - Ruzmuratova Aziza Anvarovna (Scientific Trends, 2025)
Neologisms, or newly coined words and expressions, have always played a crucial role in the evolution of language. With the rise of mass media and social networks, the pace and scale of neologism creation and dissemination have increased exponentially. This article explores the significance of neologisms in mass media and social networks, examining how these platforms influence language innovation, communication practices, and cultural trends. Drawing on linguistic theories, media studies, and digital communication research, the article analyzes the mechanisms of neologism formation and adoption, their impact on language change, and their broader social implications. The findings suggest that neologisms are vital tools for identity construction, social interaction, and reflecting contemporary societal changes, facilitated and accelerated by mass media and digital platforms.
Keywords: Neologisms, Mass Media, Social Networks, Language Evolution, Digital Communication, Linguistic Innovation, Media Linguistics.